The Contribution Of Sustainable Agricultural Development To Rationalizing Resources - The Kingdom Of Jordan As A Model - SAADI, Tarek; ZEBOUCHI, Mohamed abderraouf (جامعة الوادي - University of Eloued, 2022)
The present research paper seeks to shed light on the importance of sustainable development, particularly, sustainable agricultural development, which has become a key factor in economic development in order to follow the requirements of sustainable agricultural development, which contributes to the conservation of renewable resources. The study revealed that the solution to sustainable agricultural development has become an urgent necessity in order to obtain an environmental economy that contributes to increasing the loyalty of individuals towards their institutions that lead the wheel of the economy, ensuring the desired transition to the adoption of entrepreneurial projects in the private sector that use high agricultural technology, and the study also concluded that Jordan With limited natural resources, it must strengthen its efforts in the fields of sustainable development and resource conservation.
مقال
Keywords: sustainable development ; economic development ; environmental economy ; entrepreneurial projects ; kingdom of Jordan